Pengaruh Kecerdasan Linguistik dan Minat Belajar Terhadap Keterampilan Menyimak Berita - Dyah Widhiarsi; Sugiyo (Fahima, 2022)
The purpose of this study was to determine 1) the effect of linguistic intelligence on news listening skills; 2) the effect of interest in learning on news listening skills; 3) the influence of linguistic intelligence and interest in learning on news listening skills. A research method is the expostfacto correlation method. The research population was all SMP IT Al-Anis Sukoharjo academic year 2020/2021. The research sample is some students of SMP IT Al-Anis Sukoharjo taken by random sampling. Techniques Data collection using documentation and questionnaires. The results are 1) the influence of linguistic intelligence on news listening skills is positive and significant. It means that if students have a high level of linguistic intelligence, they can improve their listening skills well; 2) the effect of interest in learning on news listening skills is positive and significant. It means that if students have a high interest in learning, the students' news listening skills are also good; 3) there is an influence of linguistic intelligence and students' interest in learning on news listening skills, which means that there has been a correlation between linguistic, intelligence, and interest in learning (independent variable) with news listening skills (dependent variable).